Prostate Cancer Stem Cells: Clinical Aspects and Targeted Therapies - Wolf, Isis; Gratzke, Christian; Wolf, Philipp (Frontiers in Oncology, 2022)
Despite decades of research and successful improvements in diagnosis and therapy, prostate cancer (PC) remains a major challenge. In recent years it has become clear that PC stem cells (PCSCs) are the driving force in tumorigenesis, relapse, metastasis and therapeutic resistance of PC. In this minireview we introduce the PCSC hypothesis and discuss the impact of PCSCs in the clinical practice. Moreover, new therapeutic approaches to combat PCSCs are presented to combat PCSCs for a future with the aim to achieve an improved therapeutic outcome for patients with PC.